2020
DOI: 10.1053/j.jvca.2020.07.063
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series of Devastating Intracranial Hemorrhage During Venovenous Extracorporeal Membrane Oxygenation for COVID-19

Abstract: Objective: Anticoagulation may be a challenge in coronavirus disease 2019 (COVID-19) extracorporeal membrane oxygenation due to endothelial injury and dysregulation of coagulation, which may increase the risk of thrombotic and bleeding complications. This report was created to describe the authors' single institutional experience, with emphasis on the high rate of intracranial hemorrhage for the first 10 patients with COVID-19 placed on venovenous extracorporeal membrane oxygenation (VV ECMO). Design: Case ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 28 publications
3
38
1
1
Order By: Relevance
“…Whereas pulmonary embolism and deep vein thrombosis have repeatedly been documented in hospitalized COVID-19 patients [ 3 , 10 ], no study to date has examined the rate of major bleeding events. Only single-case reports [ 11 , 12 ] of massive intracerebral hemorrhage (ICH) in COVID-19 and a case series of COVID-19 patients on veno-venous extracorporeal membrane oxygenation (VV-ECMO) with 4 out of 10 patients suffering from ICH have been published [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas pulmonary embolism and deep vein thrombosis have repeatedly been documented in hospitalized COVID-19 patients [ 3 , 10 ], no study to date has examined the rate of major bleeding events. Only single-case reports [ 11 , 12 ] of massive intracerebral hemorrhage (ICH) in COVID-19 and a case series of COVID-19 patients on veno-venous extracorporeal membrane oxygenation (VV-ECMO) with 4 out of 10 patients suffering from ICH have been published [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the risk of ICH should be considered when developing an anticoagulation regimen for patients with COVID-19. Usman et al [ 83 ] reported a case series of COVID-19 patients treated with veno-venous extracorporeal membrane oxygenation (ECMO). Four of ten patients had hemorrhagic stroke, three of whom died.…”
Section: Bleeding In Patients With Covid-19mentioning
confidence: 99%
“…History of arterial HTN was reported in 89 (54%) out of 164 patients with intracranial hemorrhage, [2] , [18] , [19] , [21] – [24] , [26] , [27] , [30] [34] , [36] , [41] , [42] , [44] – [47] , [49] , [51] and in 45 (52%) out of 87 patients with ICH. [2] , [18] , [22] , [24] , [26] , [31] [34] , [36] , [41] , [42] , [44] – [47] , [49] , [51]…”
Section: History Of Arterial Hypertension and Prior Use Of Anticoagulmentioning
confidence: 99%
“…Of all 188 ICHs, 149 (79%) were primary, [2] , [18] – [28] , [30] [38] , [41] , [43] – [48] , [50] including those with or without known risk factors such as arterial HTN, prior use of anticoagulants or extracorporeal membrane oxygenation (ECMO); 29 ICHs were secondary to hemorrhagic transformation of ischemic stroke, [18] , [39] , [42] , [49] 7 to cerebral vein thrombosis, [29] , [31] and 3 to encephalitis/encephalopathy. [40] , [51] , [52] …”
Section: Etiology and Location Of Ichmentioning
confidence: 99%